2014 36th Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2014
DOI: 10.1109/embc.2014.6943823
|View full text |Cite
|
Sign up to set email alerts
|

Brain-controlled functional electrical stimulation for lower-limb motor recovery in stroke survivors

Abstract: Despite the prevalence of stroke-induced gait impairment due to foot drop, current rehabilitative practices to improve gait function are limited, and orthoses can be uncomfortable and do not provide long-lasting benefits. Therefore, novel modalities that may facilitate lasting neurological and functional improvements, such as brain-computer interfaces (BCIs), have been explored. In this article, we assess the feasibility of BCI-controlled functional electrical stimulation (FES) as a novel physiotherapy for pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 15 publications
(20 reference statements)
0
22
0
Order By: Relevance
“…The subjects averaged 8.4 BCI-FES runs per session. Almost 95 % of the total number of BCI-FES runs across all subjects and sessions were at a significant performance level (α = 0.01) compared to Monte-Carlo simulation (details in [ 24 ]; see Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The subjects averaged 8.4 BCI-FES runs per session. Almost 95 % of the total number of BCI-FES runs across all subjects and sessions were at a significant performance level (α = 0.01) compared to Monte-Carlo simulation (details in [ 24 ]; see Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, compliance with these instructions was not formally measured. The training data were recorded at 256 Hz with a NeXus-32 bioamplifier (Mind Media, Herten, Netherlands) to generate a session-specific decoding model for online operation (methods in [ 24 26 ]). This model could distinguish idling from dorsiflexion using EEG.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They suggested that the BCI-FES therapy is a safe and new gait rehabilitation option for stroke patients with severe impairments. [ 32 , 33 ] Young and colleagues also reported real-time feedback provided by using a BCI device that can be used to reward the production of certain patterns of neural activity over others. [ 8 ] The BCI-FES treatment also involves repeated attempts at functional activities to actively modulate brain activity during imagined movement, resulting in reward-based and use-dependent reinforcements and induction of neuroplastic change in the disrupted motor system.…”
Section: Discussionmentioning
confidence: 99%
“…These results are summarized in Table 2b. There are few studies investigating EEG in post-stroke patients, most of them aiming to evaluate EEG-based brain-computer interfaces (BCIs) in rehabilitation, for example detection of movement intention or stopping [131,179]. Other studies aimed to determine the best algorithms to detect FOG for example are excluded from this review.…”
Section: Electroencephalographymentioning
confidence: 99%